Challenges and prospects for dengue and malaria control in Thailand, Southeast Asia. - Corbel, V; Nosten, F; Thanispong, K; Luxemburger, C; Kongmee, M; Chareonviriyaphap, T (2013)
Despite significant advances in the search for potential dengue vaccines and new therapeutic schemes for malaria, the control of these diseases remains difficult. In Thailand, malaria incidence is falling whereas that of dengue is rising, with an increase in the proportion of reported severe cases. In the absence of antiviral therapeutic options for acute dengue, appropriate case management reduces mortality. However, the interruption of transmission still relies on vector control measures that are currently insufficient to curtail the cycle of epidemics. Drug resistance in malaria parasites is increasing, compromising malaria control and elimination. Deficiencies in our knowledge of vector biology and vectorial capacity also hinder public health efforts for vector control. Challenges to dengue and malaria control are discussed, and research priorities identified.